Usage of microbial combination degradation technology for the remediation of uranium contaminated ryegrass. (November 2020) - Jing, Luhuai; Zhang, Xianghui; Ali, Imran; Chen, Xiaoming; Wang, Li; Chen, Hao; Han, Mengwei; Shang, Ran; Wu, Yuewen
Graphical abstract: Highlight: Understanding the mechanisms of antagonism and interaction of various bacteria and fungi, while remediating the metals. Finding the best suited combination of microorganisms for Uranium remediation. Development of MCDT with ryegrass for leaching Uranium. Upscaling the bioreactor for environmental applications. Abstract: Post phytoremediation accumulation of heavy metals in plants is causing an environmental issue worldwide. In this study, we investigated the ability of eight different kinds of microorganisms to degrade and release heavy metals from heavy metal enriched ryegrass, including 5 species of bacteria ( Bacillus subtilis, Bacillus licheniformis, Bacillus pumilus -I, Bacillus pumilus -II and Bacillus cereus ) and 3 of fungi ( Phanerochaete chrysosporium, Trichoderma ressei and Pterula sp. strain QD-1), by growing them under uranium stress and assessing their ability to degrade biomass. After 30 days, the degradation ability of fungi was found better than that of bacteria, while the metal leaching ability of bacteria was found better. The highest degradation rate (upto 60%) was obtained by using P. chrysosporium, Pterula sp. strain QD-1 exhibited the best leaching rate for uranium (upto 77%). The overall degradation rate of lignin and cellulose and hemicellulose was found lower (40% and 60%, respectively). According to the antagonistic characteristics of microbes, we combined different dominant species, in which under optimal conditions the T2 combination ( P. chrysosporium, T. reesei, and Pterula sp. strain QD-1 and B. subtilis ) was able to degrade 80% of the ryegrass, 51% of lignin, 74% of cellulose and hemicellulose, releasing 78% of U, 90% of Pb and the releasing rate of other heavy metals was more than 95%. FTIR analysis showed the least degradation of lignin, while SEM-EDX analysis of the degradation residues displayed the microstructure of ryegrass being greatly damaged. Only a small amount of U was found in the residues of the researched combinations. This study provides efficient Microbial Combined Degradation Technology for heavy metal enriched biomass, which can effectively deal with heavy metal enriched plants, and provide a basis for the recovery and utilization of heavy metals, avoiding secondary pollution in the environment caused by this type of biomass.